Accelerated charge transfer of Cd0.5Zn0.5S@ZnS core–shell nano-spheres via decoration of Ni2P and g-C3N4 toward efficient visible-light-driven H2 production. Issue 19 (24th April 2020) - Ma, Xiaowei; Ruan, Qinqin; Wu, Jiakun; Zuo, Ying; Pu, Xipeng; Lin, Haifeng; Yi, Xiujie; Li, Yanyan; Wang, Lei
Abstract : Unique Cd0.5 Zn0.5 S@ZnS-Ni2 P/g-C3 N4 hybrid nano-spheres demonstrate enhanced photostability, improved light-harvesting and facilitated charge separation toward efficient H2 evolution from visible-light-driven water-splitting. Abstract : Development of noble-metal-free photocatalysts for efficient H2 production from sunlight-driven water-splitting has aroused great interest in recent years. Herein, unique Cd0.5 Zn0.5 S@ZnS core–shell nano-spheres decorated with Ni2 P and g-C3 N4 cocatalysts were prepared for the first time, and they are highly active and stable toward the visible-light-driven ( λ > 420 nm) H2 evolution reaction (HER). Noticeably, the optimized Cd0.5 Zn0.5 S@ZnS-Ni2 P/g-C3 N4 with 50 wt% ZnS, 3 wt% Ni2 P, and 8 wt% g-C3 N4 (CZ0.5 S@50ZS-3N/8CN) exhibits a superior HER activity of 55.43 mmol·g −1 ·h −1, approximately 25 and 18 times higher than those of CZ0.5 S@50ZS and Pt-decorated CZ0.5 S@50ZS (CZ0.5 S@50ZS-Pt), respectively. Meanwhile, the corresponding apparent quantum yield (AQY) at 420 nm is as high as 21%. It is revealed that the protective ZnS shell on the CZ0.5 S core enhances the photo-stability of the hybrid significantly. Moreover, the synergistic effect of the Ni2 P and g-C3 N4 cocatalysts leads to the effective transfer and separation of charge carriers. The results presented in this work may pave the way for the ingenious design and fabrication of highly active nano-structures for sufficient solar utilization.